Influence of 6 genetic variants on the efficacy of statins in patients with dyslipidemia. Issue 8 (7th May 2018) - Cano‐Corres, Ruth; Candás‐Estébanez, Beatriz; Padró‐Miquel, Ariadna; Fanlo‐Maresma, Marta; Pintó, Xavier; Alía‐Ramos, Pedro
Abstract : Background: Patients with dyslipidemia are often treated with statins to reduce lipids and hence cardiovascular risk, but treatment response is variable, partly due to genetic factors. Methods: We studied the influence of 6 gene variants (APOE c.526C > T (APOE2), APOE c.388T > C (APOE4), SLCO1B1 c.521T > C, CYP3A4 c.‐392G > A, HMGCR c.1564‐106A > G, and LPA c.3947 + 467T > C) on statin efficacy assessing 2 indicators: the percent reduction in total cholesterol (TC) and non‐HDL cholesterol (non‐HDL), as well as the achievement of therapeutic goals. The study was performed in a group of patients (n = 100) without previous pharmacological treatment. Multiple regression models were used to calculate the percentage of explanation in response variability added by every variant to a basal model constructed with significant nongenetic control variables. Results: The most influential variant was HMGCR c.1564‐106A > G (rs3846662), and carriers showed a significantly lower reduction in TC and non‐HDL. This variant is related to an alternative splicing involving exon 13, which is also regulated by lipid concentrations in patients without the variant. Concerning therapeutic goals, HMGCR c.1564‐106A > G hindered the achievement of TC targets on patients. Conclusions: The HMGCR c.1564‐106A > G variant was associated with less statin efficacy to decrease cholesterol.